ON THE ABSENCE OF SUPERCONDUCTIVITY IN GAPPED GRAPHENE SYSTEMS - GROSU, I. (Studia Universitatis Babeș-Bolyai Physica, 2018)
We analyzed the possibility of the superconducting state in the case of gapped graphene systems. For the electron excitations we consider the case of massive gapped spectrum and the case of massless gapped spectrum. Using realistic parameters we showed that the superconducting state is absent.